SHP‐1 suppresses endotoxin‐induced uveitis by inhibiting the TAK1/JNK pathway. Issue 1 (18th November 2020) - Zhuang, Xiaonan; Ma, Jun; Xu, Sisi; Sun, Zhongcui; Zhang, Rong; Zhang, Meng; Xu, Gezhi
Abstract: We investigated how Src‐homology 2‐domain phosphatase‐1 (SHP‐1) regulates the inflammatory response in endotoxin‐induced uveitis (EIU), and the signalling pathways involved. One week after intravitreal injection of short hairpin RNA targeting SHP‐1 or SHP‐1 overexpression lentivirus in rats, we induced ocular inflammation with an intravitreal injection of lipopolysaccharide (LPS). We then assessed the extent of inflammation and performed full‐field electroretinography. The concentrations and retinal expression of various inflammatory mediators were examined with enzyme‐linked immunosorbent assays and Western blotting, respectively. SHP‐1 overexpression and knockdown were induced in Müller cells to study the role of SHP‐1 in the LPS‐induced inflammatory response in vitro. Retinal SHP‐1 expression was up‐regulated by LPS. SHP‐1 knockdown exacerbated LPS‐induced retinal dysfunction and increased the levels of proinflammatory mediators in the retina, which was abrogated by a c‐Jun N‐terminal kinase (JNK) inhibitor (SP600125). SHP‐1 overexpression had the opposite effects. In Müller cells, the LPS‐induced inflammatory response was enhanced by SHP‐1 knockdown and suppressed by SHP‐1 overexpression. SHP‐1 negatively regulated the activation of the transforming growth factor‐β‐activated kinase‐1 (TAK1)/JNK pathway, but not the nuclear factor‐κB pathway. These results indicate that SHP‐1 represses EIU, at least in part, by inhibiting the TAK1/JNK pathway and suggest that SHP‐1 is a potential therapeutic target for uveitis.